2012
DOI: 10.4049/jimmunol.1103194
|View full text |Cite
|
Sign up to set email alerts
|

GITR Ligand Provided by Thrombopoietic Cells Inhibits NK Cell Antitumor Activity

Abstract: Thrombocytopenia inhibits tumor growth and especially metastasis in mice, whereas additional depletion of NK cells reverts this antimetastatic phenotype. It has therefore been speculated that platelets may protect hematogenously disseminating tumor cells from NK-dependent antitumor immunity. Tumor cells do not travel through the blood alone, but are rapidly coated by platelets, and this phenomenon has been proposed to shield disseminating tumor cells from NK-mediated lysis. However, the underlying mechanisms r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 46 publications
3
77
1
1
Order By: Relevance
“…A number of studies over the last fifteen years have clearly established that platelets protect tumor cells from natural killer (NK) cell-mediated lysis [23,[64][65][66][67]. Initial studies demonstrated that platelet-coated tumor cells were physically shielded from lysis by NKs [23], and this protection was not a result of passive agglutination but required platelet activation [64].…”
Section: Platelet-tumor Microenvironment Interaction -Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies over the last fifteen years have clearly established that platelets protect tumor cells from natural killer (NK) cell-mediated lysis [23,[64][65][66][67]. Initial studies demonstrated that platelet-coated tumor cells were physically shielded from lysis by NKs [23], and this protection was not a result of passive agglutination but required platelet activation [64].…”
Section: Platelet-tumor Microenvironment Interaction -Immune Cellsmentioning
confidence: 99%
“…Upon aggregation by tumor cells or physiological factors, platelets mobilize to their surface membrane glucocorticoid-induced TNF-related ligand (GITRL), a member of the TNF receptor superfamily and NK-inhibitory ligand[67]. Consequently, platelet-coated tumor cells are protected, in part, from NK lytic activity and IFN- secretion due to platelet GITRL interaction with its receptor GITR on NK depletion, and likely occurred as a result of platelet sequestration and ultimately secretion from -granules of tumor-derived factors that regulate bone metabolism such as TGF-1 and MMP-1.…”
mentioning
confidence: 99%
“…Several other mechanisms that enable tumours to evade NK cell-mediated surveillance have been documented. For example, tumours that activate platelets can avoid NK cell recognition, either directly by disrupting activating ligand expression 75 and displaying ligands for NK cell inhibitory receptors 76,77 , or indirectly by releasing immunoregulatory factors, such as transforming growth factor-β (TGFβ) 78 (FIG. 2).…”
Section: Nk Cell Functionsmentioning
confidence: 99%
“…Several studies have shown that platelets can protect CTCs from shear stresses during circulation, induce CTC epithelial-mesenchymal transition, and promote tumor cell extravasation to metastatic sites (7)(8)(9)(10). Neutrophils can promote adhesion and seeding of distant organ sites through secretion of circulating growth factors such as VEGF and proteases (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%